2000
DOI: 10.1038/35002588
|View full text |Cite
|
Sign up to set email alerts
|

Postsaccadic visual references generate presaccadic compression of space

Abstract: With every rapid gaze shift (saccade), our eyes experience a different view of the world. Stable perception of visual space requires that points in the new image are associated with corresponding points in the previous image. The brain may use an extraretinal eye position signal to compensate for gaze changes, or, alternatively, exploit the image contents to determine associated locations. Support for a uniform extraretinal signal comes from findings that the apparent position of objects briefly flashed around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
249
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(292 citation statements)
references
References 16 publications
39
249
4
Order By: Relevance
“…This is interpreted as a superposition of the shift and compression components of mislocalization 33,34) , such that the former reflects uniformly tilted paths while the latter reflects the shortening of spatial separation beOn the same timecourse, by contrast, the apparent positions of S1, once specified near the target (T2) position at lower trigger amplitudes, shifted in the direction opposite to that of the saccades, and then matched their veridical positions near saccade termination when the trigger amplitude was set near T2. The characteristics of mislocalization of S1 were equivalent to those reported elsewhere 23,24) , while those of Sp are new. Interestingly, if the pattern of mislocalization of Sp reflects the spatial pattern of the referent position signal Θr, its relation to the other two variables replicates the predictions of the CD theory: an error in stationary stimuli S1 (Θe) originating from a spatiotemporal misalignment of Θr with the physical eye position Θp.…”
Section: The Mirror Paradigmsupporting
confidence: 79%
“…This is interpreted as a superposition of the shift and compression components of mislocalization 33,34) , such that the former reflects uniformly tilted paths while the latter reflects the shortening of spatial separation beOn the same timecourse, by contrast, the apparent positions of S1, once specified near the target (T2) position at lower trigger amplitudes, shifted in the direction opposite to that of the saccades, and then matched their veridical positions near saccade termination when the trigger amplitude was set near T2. The characteristics of mislocalization of S1 were equivalent to those reported elsewhere 23,24) , while those of Sp are new. Interestingly, if the pattern of mislocalization of Sp reflects the spatial pattern of the referent position signal Θr, its relation to the other two variables replicates the predictions of the CD theory: an error in stationary stimuli S1 (Θe) originating from a spatiotemporal misalignment of Θr with the physical eye position Θp.…”
Section: The Mirror Paradigmsupporting
confidence: 79%
“…Honda (1999) showed that visual references can also modify the gain of the presaccadic mislocalization. Lappe, Awater, and Krekelberg (2000) recently studied saccade-induced mislocalization under various conditions. Interestingly, they found that compression of visual space as reported by Ross et al (1997) occurred only when visual references were available after the saccade.…”
Section: Discussionmentioning
confidence: 99%
“…This compression can even be perceived for natural images presented shortly during the saccade (Ross et al, 1997). Lappe et al (2000) recently studied saccade-induced mislocalization under various conditions. Interestingly, they found that compression of visual space only occurs when visual references were available after the saccade.…”
Section: Space Constancy and The Role Of Efference Copies During Saccmentioning
confidence: 99%
“…Finally, an important role of the saccade target is suggested by Ross et al (1997), demonstrating that stimuli flashed shortly before a saccade are mislocalized such that they are perceived closer to the saccade target. Whether this 'spatial attraction' by the saccade target is related to the effect of our 'reference object' mechanism that tries to anchor presaccadically attended objects on the target found after the saccade must be clarified by further research (Lappe et al, 2000).…”
Section: Postsaccadic Visual Information Affects the Use Of Transsaccmentioning
confidence: 99%